Faktor Pemberdayaan Sosial Masyarakat terhadap Konflik Sosial Masyarakat dengan Perusahaan Agribisnis PT Huma Indah Mekar Kabupaten Tulang Bawang Barat - Irawan, sahrul Ari; Safitri, Yuli; Abdurrokhim, Muhammad (Universitas Galuh, 2025)
The unavailability of sufficient land for the community to carry out various agricultural activities makes the community experience socio-economic problems that continue to occur. The lack of implementation of existing social empowerment from a company makes people feel that there is a lack of company commitment to providing social activities to the community. The non-implementation of social empowerment or CSR makes people not have a good relationship with companies which makes social conflict problems always occur. This study aims to determine the extent of CSR implementation or social empowerment that exists and the relationship between social empowerment and conflicts that occur between communities and companies. This study used descriptive analysis, with informants of as many as 18 people from parties within the company and community as well as related stakeholders. The study was conducted from March to July 2023. The results showed that the company did not implement social empowerment in the community properly. The company's empowerment programs are no longer running back. Companies can currently only carry out activities in the form of assistance or social compensation, even if the activities are at certain times. The implementation of empowerment that is not well carried out is what makes social conflict factors arise in the community and company.